Smart Microgrid approach for Distributed power generation of renewable energy - Khushi, Farha; Motakabber, S. M. A.; Ahmed Hamida, Belal; Azman, Amelia Wong; Bhattacharjee, Amit (IEEE, 2021)
The uncertainties related to renewable Smart Grid and Distribution Network is a common factor remained the underlying for every researcher. The renewable energy system has thousands of source component, and all are also located in different distance. With the time some sources may become inefficient, or any natural calamity may damage the source which causes power line faults or require schedule maintenance for better service. Some of these faults are slow developing and some are high impact. Though, the systems have safety component to suppress the issue, but affects the power generation and conduct smart grid miscalculations. A smart microgrid should have a smart Fault Location Detection and Fault Suppression unit to overcome any unnecessary burdens and uncertainties. This research modelled a smart grid system combined with a faulty detection mechanism for an efficient mechanism to overcome uncertainties. The novelty of this research is to model a SMG based on a SGC mechanism for an isolated small area, combined with a faulty detection system for an efficient mechanism to overcome uncertainties. The Faulty Location Detection (FLD) process is centered by wavelet trigger signal and mathematical morphology algorithm. In the method, the wavelet trigger signal caused by the equivalent current or voltage for a short time, travels to both terminals of the line are simulated to identify whether the fault occurs in the short branch using mathematical morphology algorithm. The modeled SMG system is divided into several segmental short branch for FLD system. Through a combined Human Machine Interface (HMI) for SMG performance and FLD monitoring process are shown for smart approach. The combined process, of SMG system modeled in MATLAB simulation platform for performance validation.